Peer Mentoring in a University Music Methods Class. Issue 2 (February 2018) - Goodrich, Andrew; Bucura, Elizabeth; Stauffer, Sandra
The purpose of this study was to investigate undergraduates' perceptions of peer mentoring and the impact of peer mentoring in a music teacher preparation course. The following questions were included: What knowledge and abilities do students bring to the peer mentoring process? How do students perceive their roles as teachers and learners in the peer mentoring experiences? How do the students benefit, if at all, from peer mentoring experiences? Students participated in four planned peer mentoring experiences; an unanticipated, informal mode of peer mentoring emerged during large-group teaching experiences. Analysis revealed that student perceptions of and comfort levels with peer mentoring varied as their roles as teacher or learner changed. Findings suggest that students use prior music and teaching knowledge when engaged in peer mentoring and their enactment of teaching roles varied depending on the structure of peer mentoring episodes. Benefits to students included increased awareness of themselves as teachers and enhanced comfort with providing and receiving critique.